A Novel Approach for Directing Transgene Expression in Drosophila: T2A-Gal4 In-Frame Fusion - Diao, Fengqiu (Genetics Society of America, 2012)
In Drosophila, the Gal4-UAS system permits a transgene to be expressed in the same pattern as a gene of interest by placing the Gal4 transcription factor under control of the gene’s DNA regulatory elements. If these regulatory elements are not known, however, expression of Gal4 in the desired pattern may be difficult or impossible. To solve this problem, we have developed a method for co-expressing Gal4 with the endogenous gene by exploiting the “ribosomal skipping” mechanism of the viral T2A peptide. This method requires explicit knowledge only of the endogenous gene’s open reading frame and not its regulatory elements.